Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan Jasa Travel - Nuraini, Ike; Mulyono, Herry; Purnama, Benni; Benediktus Rolando (Journal of Trends Economics and Accounting Research, 2024)
Because employee quality has a significant impact on an organization's performance; in a worldwide world, human resources are among the most valuable assets. Given that people are a company's or organization's most valuable asset, human resource development to generate knowledgeable personnel is highly competitive. The purpose of this study is to determine whether PT performance is significantly impacted by the work environment, work motivation, and work discipline employees. Diva Lookah Multindo Jambi. Google Forms is used in this type of quantitative research to send out questionnaires for data collection. Sampling was carried out on all PT workers totaling 46 people using a population sampling approach. The study material was analyzed using SPSS 26. The findings of this research show how elements such as work culture, work ethic, and motivation can influence how successfully PT workers execute simultaneously and partially Diva Lookah Multindo Jambi.